High Maintenance of Rhizosphere Soil C and N Equilibrium Regardless of Plant Species or Species Traits - Wakelin, Steve A.; Matson, A.; Wigley, K.; Waller, L.; Dickie, I. A.; Whitehead, David; Garrett, L. (Frontiers in Soil Science, 2021)
Factors affecting the deposition of carbon and nitrogen into the rhizosphere soil have important implications for natural and managed ecosystems. These include the invasiveness of plants, extent to which ecosystems sequester soil carbon, through to regulation of N flow within and from agricultural ecosystems. This study determined if the close elemental ratios often measured in soils are evident within the highly active rhizosphere compartment, or rather potentially emerge to a conserved ratio (over time) from different initial rhizosphere states. Towards this, we assessed the rhizosphere C and N content (and C:N ratio) of 37 plant species; these were further grouped into the categories provenance (native or exotic to New Zealand), form (forb, grass, shrub, or tree), root-based nitrogen fixation symbiosis (+/- N-fixation), or mycorrhization type. Furthermore, the potential nitrification rate (PNR) among the plant rhizosphere soils was quantified to explore relationships between nitrate formation and the total C and C:N ratio. Mycorrhization status, provenance, and form had no significant influence on nutrient status nor PNR in rhizosphere soil samples (p>0.05). However, total C and total N were significantly increased in the rhizosphere of N-fixing species (p<0.02). These increased in proportion, with the C:N remaining constant for both groups (~12.24; p=0.79). Rhizosphere PNR did not vary with categories of plants tested and had no correlation to rhizosphere total C, total N, nor C:N ratio (p>0.3 for all). Overall, this study showed that conservation of nutrient ratios often measured in soils are present within the rhizosphere, where initial inputs of C and N enter the soil ecosystems. With the exception of N-fixing plant species, the rhizosphere soils retain remarkably high conservation in C, N, C:P, and PNR among key groupings.